SUCCESSION OF MAIZE WITH SOME WINTER CROPS 2 – EFFECTS ON MAIZE AND WINTER CROP CHARACTERS - & et al., Sadalla (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The experiments were conducted during two fall season and two winters (2010 and 2012), at Grdarash Research Station in Erbil, Kurdistan Region of Iraq. Four winter crops were chosen Wheat, Canola, Pea, Broad bean as well as Fallow plot. These crops were planted in Randomized Complete Block Design with three replications during both winter seasons. Maize was planted during the fall seasons succeeded by winter crops. Some field characters were recorded for each winter and fall maize crops during the four growing seasons. The result revealed that all the characters value of winter crops were decreased. The reduction were in 2011-2012 season about 58.92% in wheat number of tillers 45.20% and 57.67% in plant height and yield in broad bean respectively, and 39.60% in pea yield. Fall season 2011 maize showed significant differences for the characters ear height, 250 kernel weight and yield. While in fall season 2012 only ear height and ear length had significant differences.